PEMBERDAYAAN JAMAAH MELALUI PENDIDIKAN LIFE SKILLS PADA MASJID AL-ANWAR GONDANG WONOSOBO (Penamas, 2021)
This research is motivated by the large number of mosques in Indonesia that have complete facilities, but the management of these facilities is used more to generate mosque income alone, and its use tends to be more on the aspects of worship, social, formal education and daâ€™wah less emphasis on empowering and involving jamaah in various aspects especially in life skills education. This paper aims to find out how the implementation of life skills education is held at Al-Anwar Mosque and how it affects the socio-economic conditions of pilgrims. Data collection is done by interview, observation, and study documentation. The results showed that there were several life skills education taught and transformed by Al-Anwar mosque to the audience including cinematography, photography, graphic design, MC Javanese language skills (pranoto adicoro), and coffee processing with the brand â€œPereng Gantungâ€. Also, the mosque makes the Digital Mosque program. Takmir provides various facilities such as fingerprint, trigger, free wifi, and website. The results of the study concluded, first, the Al-Anwar mosque functions not only as a place of worship, preaching, and education but as a place for life skills education. Second, life skills education at Al-Anwar Mosque is supported by several factors including the innovation of young management, support from community leaders, and digital mosque programs. Third, life skills education held at Al-Anwar Mosque affects improving the pilgrimâ€™s economy.
Keywords: Pemberdayaan jamaah, pendidikan life skills, masjid